Menggagas Model Proyeksi Penerimaan PKB dan BBNKB - ROSDIANA, HAULA (UI Scholars Hub, 2011)
Local Tax Offices usually use linear model to forecast revenue from vehicle tax (Pajak Kendaraan Bermotor /PKB) and vehicle ownership transfer fee (Bea Balik Nama Kendaraan Bermotor/BBNKB). They only employ macroeconomic factors, such as inflation, economic growth and foreign exchange rate. Actually, there are non macroeconomic elements that can influence regional government revenue from PKB and BBNKB. PKB depends on the amount of vehicles in the region. The preference to use mass transportations and regional government policies to minimize number of cars affects the number of vehicles. The tax objective of BBNKB is to transfer ownership of new or old vehicle. So, besides buying power factor, the pattern of people to choose between motorcycle or car, and migration of people will affect regional government revenue. The result shows the alternative model of forecasting PKB and BBNKB revenue by taken into account the non macroeconomic factors that influence people preferences to buy vehicle and preferences to use mass transportation instrument.